2014
DOI: 10.1021/cs501592f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wild-Type Cytochrome P450BM3 by the Next Generation of Decoy Molecules: Enhanced Hydroxylation of Gaseous Alkanes and Crystallographic Evidence

Abstract: The direct hydroxylation of alkanes under mild conditions is a key issue in catalytic chemistry that addresses an increasing number of industrial and economic requirements. Cytochrome P450s are monooxygenases that are capable of oxidizing less reactive C−H bonds; however, wild-type P450s are unavailable for many important nonnative substrates such as gaseous alkanes. Here, we report the enhanced hydroxylation activities and crystallographic evidence for the role of decoy molecules in wild-type P450BM3-catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 43 publications
(83 reference statements)
3
76
0
8
Order By: Relevance
“…[9] Fore xample,p ropane was efficiently hydroxylated by P450BM3 with the assistance of N-perfluorononanoyl-l-leucine (PFC9-l-Leu). [9] Fore xample,p ropane was efficiently hydroxylated by P450BM3 with the assistance of N-perfluorononanoyl-l-leucine (PFC9-l-Leu).…”
mentioning
confidence: 99%
“…[9] Fore xample,p ropane was efficiently hydroxylated by P450BM3 with the assistance of N-perfluorononanoyl-l-leucine (PFC9-l-Leu). [9] Fore xample,p ropane was efficiently hydroxylated by P450BM3 with the assistance of N-perfluorononanoyl-l-leucine (PFC9-l-Leu).…”
mentioning
confidence: 99%
“…Crystallography studies have revealed the role of decoy molecules in reshaping the active site of P450s. The co‐crystal structures of NADPH‐dependent P450BM3 bound to decoy molecules clearly indicate that perfluorononanoic acyl l ‐phenylalanine (PFC9‐ l ‐Trp) and Z‐ l ‐Pro‐ l ‐Phe partially occupy the native substrate tunnel and form a new pocket of reduced size (Figure A, B). This pocket allows the enzyme to accept smaller substrates, such as small alkanes and benzene.…”
Section: Decoy Molecule Strategymentioning
confidence: 77%
“…The catalytic turnover numbers were found to be dependent on the chain length of the PFCs. Although ethane was hydroxylated under high pressure with PFCs, and at normal pressure with amino acid‐modified PFCs (PFCs‐amino acids), the current system was not able to oxidize methane …”
Section: Decoy Molecule Strategymentioning
confidence: 99%
“…[155] Hydroxylation rates of,r espectively 45 min À1 P450 À1 and 256 min À1 P450 À1 could be achieved with N-perfluorononanoyl-l-leucine. Theb inding of as ubstrate activates the enzyme to perform the oxidation reaction, which in itself can be quite aselective.Byadding an inert decoy molecule that binds and thereby activates the enzyme,c atalytic turnover for an onnative non-binding substrate might be achieved.…”
Section: Reviewsmentioning
confidence: 95%